If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + y(2x) = 0 Remove parenthesis around (2x) 2x + y * 2x = 0 Reorder the terms for easier multiplication: 2x + 2y * x = 0 Multiply y * x 2x + 2xy = 0 Solving 2x + 2xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '2x'. 2x(1 + y) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + y)' equal to zero and attempt to solve: Simplifying 1 + y = 0 Solving 1 + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + y = 0 + -1 y = 0 + -1 Combine like terms: 0 + -1 = -1 y = -1 Add '-1y' to each side of the equation. y + -1y = -1 + -1y Combine like terms: y + -1y = 0 0 = -1 + -1y Simplifying 0 = -1 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| x-(5x-5)=13 | | 5/6(12x-6)-4(3x-1)=0 | | -5(y-6)=5y-30 | | x-532=-32 | | 12v^2=27+27v | | 19b-10=35b+b | | -18=-24-9-15 | | 6x-6y=-1 | | -2(2x-2)=-4x-4 | | 12x^3-13xy-14y^2= | | -x-(13+4x)=-3(5-9x) | | 19b+10=35b+b | | 1t^2-1=0 | | 2u^2+2u-3=0 | | 3(y+2)=-2(y-3) | | 2x-y(2x)= | | -4x+19=-7(x-4) | | 24=2x+14 | | 3y^3-12y^2+6y-24=0 | | 1.8+7n=5.9-4n | | 18x^3=2x | | h^2+81=3 | | 6x-2=4x+5 | | 64=40+3x | | 4z-5=3 | | -2x^2-8x-14=-6 | | 7(v-5)=4v-47 | | 16a^3b^2+4a^2b^2-12ab-4ab^2= | | x+88=5x+40 | | -12=x-13 | | 2(4+x)-4x-2x=28-6x | | x-2x+5=-5 |